An unusual detection of 2‐amino‐3‐(2‐chlorobenzoyl)‐5‐ethylthiophene and 2‐methylamino‐5‐chlorobenzophenone in illicit yellow etizolam tablets marked "5617" seized in the Republic of Ireland. Issue 3 (7th December 2021) - Downey, Carol; O'Donnell, Audrey; McLaughlin, Gavin; O'Neill, Geraldine; O'Brien, John; Kavanagh, Pierce V.
Abstract: Benzodiazepines are a class of compounds used clinically to treat a variety of conditions including anxiety and insomnia. Their potential for abuse has led to a surge in their availability on the illegal drugs market. End users often rely on markings on illicit tablets to identify their contents. However, falsified tablets mimicking genuine pharmaceutical preparations often contain ingredients that differ from what people believe they are taking. The absence of any quality control of the content, purity, or strength of fake tablets can result in adverse effects or even fatal outcomes. In recent years, drug seizures involving illicit round yellow tablets marked "5" on one side and "5617" below a scoreline on the reverse have been submitted to Forensic Science Ireland (FSI) by An Garda Síochána (Irish Police) from throughout the Republic of Ireland. These findings relate to 26 different seizures; the cumulative tablet total seized was in excess of 20, 000, and the total number of tablets of this description analyzed at FSI was 141. Irish users assume that the active ingredient present was diazepam. The qualitative analytical results for these tablets are reported. All tablets were found to contain 2‐methylamino‐5‐chlorobenzophenone. In addition, the tablets contained either 2‐amino‐3‐(2‐chlorobenzoyl)‐5‐ethylthiophene or etizolam or both. The constituents were present in varying relative amounts in visually similar tablets. Neither 2‐amino‐5‐chlorobenzophenone nor 2‐amino‐3‐(2‐chlorobenzoyl)‐5‐ethylthiophene had previously been found in tablets analyzed at FSI. Abstract : Visually similar round yellow tablets marked "5617" below a scoreline on one side and "5" on the reverse were found to contain 2‐methylamino‐5‐chlorobenzophenone in combination with 2‐amino‐3‐(2‐chlorobenzoyl)‐5‐ethylthiophene and/or etizolam in varying proportions. 2‐Methylamino‐5‐chlorobenzophenone is known to be both an intermediate in the synthesis of diazepam and also one of its degradation products, whereas 2‐amino‐3‐(2‐chlorobenzoyl)‐5‐ethylthiophene has been reported as an intermediate in the synthesis of etizolam but not as a breakdown product. Online discussions reveal that users believe the illicit tablets to be a new preparation containing diazepam.